Politics and trade unions in Argentina, Brazil and Uruguay in the XX century (Colección, 2018)
The turn of the century in Argentina, Brazil and Uruguay was a new political turn, given the access to power of political forces with roots or links with organized labor. In this sense, this paper aims to describe the main characteristics that acquire the relationship between politics and trade unionism throughout the twentieth century in the three countries to observe the main similarities and differences between cases. This will show us, how the genesis conditions and development mechanisms and positive reinforcement of the link foretells a pattern or path to a turn or change of time, to a configuration of a political opportunity structure for access to the government of political forces with bases in the labor movement historically.
Keywords: Trade Unions; Politics; Argentina; Brazil; Uruguay